Inappropriate prescribing in older residents of Australian care homes - Stafford, Andrew; Alswayan, M.; Tenni, P. (Wiley-Blackwell Publishing Ltd., 2011)
What is known and objective: The incidence of inappropriate prescribing is higher amongst the older age group than the younger population. Inappropriate prescribing potentially leads to drug-related problems such as adverse drug reactions. We aimed to determine the prevalence of inappropriate prescribing in residents of Tasmanian (Australia) residential care homes using Beers and McLeod criteria. Methods: Patient demographics, medical conditions and medications were collected from medical records. The patients who fulfilled either Beers or McLeod criteria were identified and the characteristics of these patients were then compared. Results: Data for 2345 residents were collected between 2006 and 2007. There were 1027 (43•8%) patients prescribed at least one inappropriate medication. Beers criteria identified more patients (828 patients, 35•3%) as being prescribed inappropriate medication compared with McLeod criteria (438 patients, 18•7%). Patients taking psychotropic medication/s, more than six medications or diagnosed with five or more medical conditions were more likely to be prescribed an inappropriate medication (P < 0•001). The most frequently identified inappropriate medications included benzodiazepines, amitriptyline, oxybutynin and non-steroidal anti-inflammatory drugs.What is new and conclusion: Inappropriate prescribing, as defined by either Beers criteria or McLeod criteria, is relatively common in Australian nursing homes. The prevalence of inappropriate prescribing, and factors influencing it, are consistent with other countries. Both Beers and McLeod criteria are a general guide to prescribing, and do not substitute for professional judgment.